Perbandingan Konstitusional Pengaturan Impeachment Presiden Antara Indonesia Dengan Jerman - Adella Anindia; Rosmini; Poppilea Erwinta (Fakultas Hukum Universitas Mulawarman, 2021)
The impeachment system in Germany is implemented slightly differently from that applied in Indonesia. The impeachment system in Germany is executed by the Constitutional Court whose decision is final, which means that it does not receive a 2/3 proposal from the Bundestag and the Bundestraat regarding the dismissal of the President and Vice President as in Indonesia. The regulation of the impeachment system in a country needs to be studied by involving a comparison country to find out whether the impeachment system in a country runs optimally and ideally. Comparison of Impeachment between Indonesia and Germany, The mechanism for dismissing the president as regulated in the constitution is an affirmation that the Republic of Indonesia is a state of law, this is a step forward in a constitutional perspective so that impeachment of the president based on non-juridical factors alone does not happen again in the future. dismissal of the president as regulated in the 1945 Constitution, because in the impeachment mechanism, the decision of the Constitutional Court confirming the opinion of the DPR is not binding. Keywords: president impeachment; constitutional law; comparative law.